THE AGE FEATURES OF MORPHOLOGICAL CHANGES OF THE PITUITARY-NEUROHYPOPHYSIS SYSTEM IN THE LATER STAGES OF STREPTOZOTOCIN DIABETES - Zhurakivska O.Уа. (World of Medicine and Biology, 2012)
The research is devoted the study of morphofunctional organization of pituitary- neurohypophysis system in the later stages of streptozotocin diabetes. To study it was used the hypothalamus and neurohypophysis of 40 Wistar male rats of 3 - and 24-months. In the later stages of streptozotocin diabetes in 24 months animals the vacuoles dystrophy of neurosecretory cells, the gliocytes resorption of affected neurons, significant decrease in bulk density neurosecretory granules in light and dark cells of investigated nuclei compared with controls (p